O Cerrado e o agronegócio: desafios para o desenvolvimento sustentável e as políticas ambientais (1973-2023) - Ribeiro, Idelmar da Silva (2025)
Responsible economic exploitation of natural resources is one of the greatest challenges of the century, since the management of increasingly scarce environmental resources is at odds with the ever-increasing need for commodities to feed a growing population. In this sense, in a competitive and more demanding environment, the search for sustainable development becomes the focus of attention. Therefore, this paper seeks to address the relationship between agricultural development and environmental preservation and its laws, taking the State of Goiás as a geographic focus, since it is an agricultural state located in the Cerrado biome, which has shown great development in the last 50 years, our time frame, driven mainly by the agronomic development observed in this period. In this context, we sought to inventory the development of agricultural and environmental laws at the national and local levels, as well as contextualize the main factors that influenced agricultural development, such as public policies for regional development, technological innovations provided mainly by the Brazilian Agricultural Research Corporation (EMBRAPA) and the Goiana Agricultural Research Corporation (ENGOPA), as well as the influence of migration from the south and the introduction of crops such as soybeans in this context. As a result, four historical moments in the relationship between agricultural laws and environmental laws were identified, each with its own specific characteristics, in addition to a schematic model that shows how environmental laws developed before the 2000s and how this development occurred after the 2000s. It can also be seen that, although they may sometimes seem conflicting and even antagonistic, there is an increasing intertwining between the environment and agricultural development, with the state as the major mediator and economic interests as the main actor in this relationship.